'No-one else wears one:' Exploring farmer attitudes towards All-Terrain Vehicle helmets using the COM-B model. (June 2022) - Irwin, Amy; Mihulkova, Jana; Berkeley, Stephanie; Tone, linca-Ruxandra
Highlights: All-Terrain Vehicles (ATVs) are linked to farming fatalities and injuries every year. However, despite evidence that wearing a helmet reduces the risk of serious injury, few farmers wear them. This study assessed farmer attitudes to ATV helmets using the Michie COM-B model. Participants reported a range of barriers to helmet wearing including the perception that helmets could interfere with work activities, social stigma and perceived exemption from harm. Key interventions are suggested using the Michie behaviour change wheel, including modelling, raising awareness and training. Abstract: Introduction: All-Terrain Vehicles (ATV) are a popular piece of farming machinery but are linked to many fatalities and injuries every year. Despite evidence that ATV helmets reduce the risk of serious or fatal injury, research suggests that few farmers wear them. The aim of this study was to explore farmer attitudes toward ATV helmets, using the COM-B model as a framework to identify key barriers and enablers of helmet use and suggest potential interventions to increase helmet use in agriculture. Methods : A mixed-methods online survey featuring quantitative and qualitative questions was used to explore key attitudinal factors relevant to farmer helmet wearing. A total of 211 UK and Irish farmers were recruited, including farm owners, managers, workers, and contractors. Results : Personal exemption from risk, emotional benefits, cognitive barriers, and guideline prompts were all found to be significant predictors of farmer helmet wearing. Key categories within the qualitative data indicated that helmet properties, risk perception, farming culture, and the farming environment could all function as barriers to helmet wearing. Suggested enablers of helmet use included increasing helmet availability and enhancing awareness of the consequences of ATV accidents. Conclusions : The key barriers and enablers presented within this paper highlight the relevance of capability (helmet design, time pressure), opportunity (social norms), and motivation (perceived control of risk) when considering farmer helmet wearing behaviors. In order to encourage farmers to wear helmets it will be necessary to design specific interventions using the behavior change wheel. Practical applications : Key interventions to prompt helmet use include the inclusion of more cues to prompt helmet wearing (e.g., stickers on the ATV), enhanced training and education, and modelling (e.g., key farming figures shown to wear helmets in the media).